Challenges of Enforcement of Forestry Legislation in Taraba State, Nigeria - Y.M, Ahmed; E.D, Oruonye (International Journal of Geography and Geology, 2017)
Forests are essential resources for human survival and well-being. Within developing countries, millions of extremely poor people depend on forest resources for their livelihoods and security. The forest resources of Taraba State has witnessed high timber and fuelwood exploitation, bush burning, expansion of farmlands and grazing activities. Despite the existence of forest legislation in the state, illegal logging and indiscriminate forest resource exploitation has continued to increase at alarming rate. This makes it imperative to reappraise the forestry legislation in the state and the challenges of effective enforcement of these legislations. Data were generated from secondary materials, personal observation and interviews with officials of the Department of Forestry. The study findings shows that with increase in population, people need to expand their settlements and require more lands to cultivate in order to meet increasing food requirement. This leads to encroachment into forestry reserve. Poor logistics and weak institutional framework hampers the capacity of the forestry officials to enforce forestry legislation. This has resulted in the depletion of Forest resources particularly timber and woody plant resources. Some of the problems includes lack of political will on the part of government, underfunding, lack of or dilapidated office/accommodation, inadequate manpower, lack of equipment, lack of capacity building, Government preference and emphasis on revenue generation as against biodiversity conservation, Conspiracy of forestry officers, village heads and chiefs with merchant timber loggers, lack of effective supervision, coordination and enforcement of forest legislations. The study recommends the need for the government to be more proactive on the issues of enforcement of forestry legislation.